Effects of vitamin D supplementation on symptoms of depression in overweight and obese subjects: randomized double blind trial - Jorde, R.; Sneve, M.; Figenschau, Y.; Svartberg, J.; Waterloo, K. (Journal of internal medicine, 2008)
. Objectives.  The objective of the present study was to examine the cross‐sectional relation between serum 25‐hydoxyvitamin D [25‐(OH) D] levels and depression in overweight and obese subjects and to assess the effect of vitamin D supplementation on depressive symptoms. Design.  Cross‐sectional study and randomized double blind controlled trial of 20.000 or 40.000 IU vitamin D per week versus placebo for 1 year. Setting.  A total of 441 subjects (body mass index 28–47 kg m−2, 159 men and 282 women, aged 21–70 years) recruited by advertisements or from the out‐patient clinic at the University Hospital of North Norway. Main outcome measures.  Beck Depression Inventory (BDI) score with subscales 1–13 and 14–21. Results.  Subjects with serum 25(OH)D levels <40 nmol L−1 scored significantly higher (more depressive traits) than those with serum 25(OH)D levels ≥40 nmol L−1 on the BDI total [6.0 (0–23) versus 4.5 (0–28) (median and range)] and the BDI subscale 1–13 [2.0 (0–15) versus 1.0 (0–29.5)] (P < 0.05). In the two groups given vitamin D, but not in the placebo group, there was a significant improvement in BDI scores after 1 year. There was a significant decrease in serum parathyroid hormone in the two vitamin D groups without a concomitant increase in serum calcium. Conclusions.  It appears to be a relation between serum levels of 25(OH)D and symptoms of depression. Supplementation with high doses of vitamin D seems to ameliorate these symptoms indicating a possible causal relationship.